Cambridgeshire appendix - Rumble, Alexander (The University of Hull)
The appendix records the lists of jurors who represented the Cambridgeshire Hundreds during the Domesday Survey. The information is supplied by the Inquisitio Eliensis (Ely Enquiry) and the "Inquisitio Comitatus Cantabrigiensis" (Cambridgeshire Enquiry, or ICC). This appendix is taken from the Phillimore printed edition (1981) edited by Alexander Rumble and has been lightly revised by Caroline and Frank Thorn.